CONFIRMATION BIAS, SELF-ATTRIBUTION BIAS, DAN OVERCONFIDENCE DALAM TRANSAKSI SAHAM - Supramono Supramono; Marisa Wandita (University of Merdeka Malang, 2017)
Overconfidence caused investors to overestimate their knowledge, underestimate risk and exaggerate their ability to control events. This led to excessive trading, unwarranted risk-taking, and ultimately, financial losses. The aim of this study was to analyze the relationship between overconfidence and confirmation bias and self-attribution bias. The subjects in this experiment were 53 students in finance classes at the Faculty of Economic and Business. Data that had been collected was analyzed using descriptive and inferential analysis techniques using bivariate correlation. The result of this study showed that there was a positive relationship between confirmation bias and overconfidence. However, there was no positive relationship between self-attribution bias and overconfidence.